2015
DOI: 10.1177/0194599815591810
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Apoptotic vs Antiapoptotic Proteins in Middle Ear Cholesteatoma

Abstract: The upregulation of c-FLIP together with unchanged p53 suggests an altered equilibrium between apoptosis and antiapoptosis, favoring antiapoptosis, and may play a role in the pathogenesis of cholesteatoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
5
2
Order By: Relevance
“…To evaluate cell proliferation in our study, Ki-67 and NF-κβ were used. Even though many authors show that Ki-67 is upregulated in cholesteatoma [46,47], our results did not show statistically significant results between groups. Similar results with no statistically significant difference of Ki-67 in cholesteatoma compared to skin were presented by Kim et al [48] and Kuczkowski et al [49].…”
Section: Discussioncontrasting
confidence: 99%
“…To evaluate cell proliferation in our study, Ki-67 and NF-κβ were used. Even though many authors show that Ki-67 is upregulated in cholesteatoma [46,47], our results did not show statistically significant results between groups. Similar results with no statistically significant difference of Ki-67 in cholesteatoma compared to skin were presented by Kim et al [48] and Kuczkowski et al [49].…”
Section: Discussioncontrasting
confidence: 99%
“…That probably might suggest the specific stage of disease with a decrease in cellular activity. However, this data was different from other studies where Chung et al[35] and Hamed et al[36] proved overexpression of Ki-67 in cholesteatoma tissue compared to skin epithelium. This might be explained by the fact that Hamed and other authors took control skin from the same patients, who had cholesteatoma.…”
contrasting
confidence: 96%
“…Many previous reports found that Ki-67 was overexpressed in the cholesteatoma epithelium compared to the normal retroauricular and meatal skin [ 8 , 19 - 22 ]. In contrast to these results, Kuczkowski et al [ 23 ] failed to find any significant difference in Ki-67 expression between 51 cholesteatomas and 6 meatal skin tissues.…”
Section: Discussionmentioning
confidence: 99%